The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/labinvest.3700260
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma induction of gastric mucous neck cell hypertrophy

Abstract: Chronic inflammation of the gastric epithelium is believed to induce mucosal changes that can eventually develop into gastric cancer. In gastrin-deficient (GÀ/À) mice exhibiting chronic inflammation in the hypochlorhydric stomach, we documented a prominent fundic mucous cell lineage sharing morphological similarity with preneoplastic changes reported in Helicobacter-infected mice. To study the identity and origin of this cell lineage, we screened for different gastric mucosal cell markers. The clusters of larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 40 publications
5
64
0
5
Order By: Relevance
“…Kang et al (54) found that the human gastric cell line NCI-N87 acquired mucous neck cell traits upon treatment with IFN-␥ such as secretion of mucus and expression of the mucin MUC6, TFF2, and pepsinogen II. Infusion of IFN-␥ into wildtype mice was further shown to induce expansion of the mucous neck cell compartment in vivo, probably by triggering the deregulated proliferation of this cell type (54).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (54) found that the human gastric cell line NCI-N87 acquired mucous neck cell traits upon treatment with IFN-␥ such as secretion of mucus and expression of the mucin MUC6, TFF2, and pepsinogen II. Infusion of IFN-␥ into wildtype mice was further shown to induce expansion of the mucous neck cell compartment in vivo, probably by triggering the deregulated proliferation of this cell type (54).…”
Section: Discussionmentioning
confidence: 99%
“…Third, deletion of the gene encoding the Th1 cytokine IFN-γ protects mice from gastric atrophy induced by infection with Helicobacter spp., whereas deletion of the gene encoding the Th2 cytokine IL-4 leads to more severe atrophic gastritis (75). Finally, infusion of IFN-γ into C57BL/6 mice can induce metaplasia and SPEM (76), whereas pretreatment of mice with IL-4 prevents the development of atrophic gastritis after infection with Helicobacter spp. (77).…”
Section: Host Factors That Affect the Development Of Gastric Cancer Gmentioning
confidence: 99%
“…39, 40 Yamaoka et al 41 investigated the chronological changes in cytokine profiles during Hp infection in gerbils and reported that mucosal IFN-g mRNA reached maximal levels at 4 weeks and remained high thereafter. Kang et al 42 reported that IFN-g induces expression of MUC6 and TFF2, and lymphocytes infiltrating into the mucosa were IFN-g positive. Shibata et al 43 reported CagA protein may be essential for the induction of IFN-g and IL-1b and infiltration of inflammatory cells.…”
Section: Spem Specifically Arises In and Spreads Out From The Intermementioning
confidence: 99%